THE INFLUENCE OF MARKETING COMMUNICATION, CUSTOMER EXPERIENCE, AND RELATIONSHIP MARKETING ON CUSTOMER SATISFACTION (Case Study on Havana Garden Cafe, Bireuen Regency) - Sarah Nurfadilla C; M. Subhan; Mariyudi; Teuku Zulkarnaen (RADJA PUBLIKA, 2025)
This study aims to see the Influence of Marketing Communication, Customer Experience, and Relationship Marketing on Customer Satisfaction (Case Study on Havana Garden Cafe, Bireuen Regency). The sampling technique in this study is NonProbability Sampling. The sample in this study was 125 visitors to the Havana Garden Cafe, Bireuen Regency. Primary data in this study were taken by means of interviews and distributing questionnaires. The analysis tools used are multiple linear regression analysis methods, classical assumption tests, instrument tests (validity and reliability), hypothesis testing, and determination coefficients using the SPSS version 25 program. The results of this study show that the marketing communication variable (X1) has a significant positive effect on customer satisfaction (Y), the customer experience variable (X2) has a negative and insignificant effect on customer experience (Y), and relationship marketing (X3) has a negative and insignificant effect on customer experience (Y). The data was processed statistically using the SPSS 25 program tools.